Management of severe hemoptysis. (3rd October 2018) - Parrot, Antoine; Tavolaro, Sebastian; Voiriot, Guillaume; Canellas, Antony; Assouad, Jalal; Cadranel, Jacques; Fartoukh, Muriel
ABSTRACT: Introduction : Though rare, severe hemoptysis (SH) is associated with a mortality rate exceeding 50% when not managed properly. Areas covered : This paper reviews the recent epidemiological data regarding SH, the role of multidetector computed tomography angiography (MDCTA), and fiberoptic bronchoscopy (FOB) in its management, as well as the value of current treatments. Expert commentary : MDCTA is becoming an essential modality, since it allows determining the location, etiology, and mechanism of the bleeding. FOB can be delayed, except when local control of bleeding is required. Emergency treatment relies on interventional radiology. Both bronchial and non-bronchial arteries should be explored during bronchial arteriography. Surgery must be considered in all operable patients if the cause of hemoptysis persists.